The Social Nature of Eating. Issue 4 (July 2015) - Morin, Karen H.
Abstract : Have you ever noticed that you tend to eat more when in the company of others? Have you ever wondered why this happens? Our nutrition expert Dr. Morin explains eating and social behavior.